2020
DOI: 10.1177/0300060520943420
|View full text |Cite
|
Sign up to set email alerts
|

Associations between hepatocellular carcinoma risk and rs3212227 and rs568408 polymorphisms: a systematic review and meta-analysis

Abstract: Background Interleukin-12 (IL-12) is considered to be a risk factor for cancer; however, its role in hepatocellular carcinoma (HCC) remains unknown. This study aimed to explore the impacts of the IL-12 rs3212227 and rs568408 gene polymorphisms on HCC. Methods We searched PubMed, Embase, Web of Science, and Chinese Knowledge Infrastructure databases for studies on the associations between HCC and IL-12 rs568408 and rs3212227 polymorphisms published prior to 1 May 2020. The effects of the polymorphisms on HCC su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…IL-12B rs3212227 polymorphism is crucial for the development of cancer because the A > C allele can decrease cytokine levels (do Carmo Vasconcelos de Carvalho et al, 2012). Consistent with a previous meta-analysis study on hepatocellular carcinoma (Kong et al, 2020), in our study, haplotype analysis of GG+GG in IL-12A and IL-12B yielded an elevated risk for oral cancer.…”
Section: Discussionsupporting
confidence: 90%
“…IL-12B rs3212227 polymorphism is crucial for the development of cancer because the A > C allele can decrease cytokine levels (do Carmo Vasconcelos de Carvalho et al, 2012). Consistent with a previous meta-analysis study on hepatocellular carcinoma (Kong et al, 2020), in our study, haplotype analysis of GG+GG in IL-12A and IL-12B yielded an elevated risk for oral cancer.…”
Section: Discussionsupporting
confidence: 90%
“…In head and neck cancer, P2RY14 is also a potential biomarker for immune regulation of the tumor microenvironment and good prognosis (42). In addition, more meta-analyses have shown that potentially functional polymorphisms of IL12A and IL12B are thought to increase the risk of malignancies such as gastric, lung, and cervical cancers (43)(44)(45). TLL1 is significantly upregulated in OC patients and has been suggested as a prognostic marker in OC patients (46,47), and the same results were obtained in our study.…”
Section: Discussionmentioning
confidence: 99%